(untitled) (International Journal of Current Engineering and Technology, 2015)
Burkina Faso is facing tremendous challenges for its water and agricultural sector considering temperature and floods which increased during the previous decades and given IPCC climate projections for West Africa. Addressing the lack of knowledge on climate trends at local scale, this paper assesses trends in rainfall as well as means Temperature (Tmean) from 1971 to 2050 in the Massili basin. Hence, a 50 years record (1961-2011) from Gonse station as well as data from four Regional Climate Models (MPI-M-MPI-ESM-LR, CCCma-CanESM2, AFR 44 and AFR MPI) was analyzed. The model data were extracted from the Coordinated Regional Climate Downscaling Experiment (CORDEX) data and included historical runs (1971-2005) and two representative concentration pathways scenarios (RCP4.5 and RCP8.5) for the period 2006-2050, all at 50*50 km² spatial resolution. The analysis of the simulation data and their comparison with the observed record indicate that only AFR 44 reproduce well the climate trend sufficiently. However, a bias correction was done for improvement. AFR 44 data predict an increase of Tmean by 1.8 ° C (RCP4.5) and 3.0 °C (RCP8.5). With an increase of 7.5 mm (RCP8.5) and an increase of 14.8 mm (RCP4.5) until 2050, both rainfall scenarios from AFR 44 provide increasing estimates.